P24 Enablers and barriers in referral and uptake of pulmonary rehabilitation (PR) in a south asian patient group with COPD: a qualitative study. (12th November 2019) - Fox, SE; Early, F; Wilson, PM; Deaton, C; Haque, HW; Ward, JR; Fuld, JP
Abstract : Introduction: Pulmonary rehabilitation (PR) referral and uptake in the UK remains low despite being a high value treatment for COPD. The referral rate and uptake of PR in South Asian populations is known to be particularly reduced and reasons for this are poorly understood. This mixed methods study explored barriers and enablers for PR referral and uptake in a sub-group of South Asian (SA) patients and their clinicians. Methods: Interviews were conducted with White British (n=35) and SA (n=7) patients with COPD and with Health Care Professionals (4/38) working with SA patients. A deductive coding framework informed by Normalisation Process theory and supplemented by inductive codes was used. Codes were applied across the whole study and grouped into categories for analysis and comparison. Results: Six domains of enablers and barriers were identified; patient factors for accepting and declining, primary care and patient interface, factors within primary care, patient's first interaction with PR and factors within PR course. Specific barriers and enablers emerged across all domains in the SA patient group: Perceived barriers for accepting PR referral included poor understanding of PR, unfamiliarity with healthcare models and physiotherapy as a treatment option, and guilt and shame related to smoking. A specific enabler of attendance was a strong belief in what doctors say. Within the primary care–patient interface, language and patient interactions via the family unit were perceived barriers. Within primary care, data was not specifically collected on SA referral/uptake of PR hence gaps would not be identified. Information on patient translator needs not being conveyed to PR services ahead of patient assessment was identified as a barrier. Within the PR course, both positive aspects and potential challenges of having a translator present in groups were reported. Conclusions: Identification of specific factors that are perceived to influence PR referral and uptake for South Asian patients have important practical implications for increasing PR uptake and addressing this health inequality. Further research should seek to find effective ways of addressing the particular needs of this group.